2016
DOI: 10.1080/08997659.2016.1223207
|View full text |Cite
|
Sign up to set email alerts
|

First Record of Fibropapillomatosis in a Green Turtle Chelonia mydas from the Baja California Peninsula

Abstract: Fibropapillomatosis (FP) is characterized by multiple fibroepithelial tumors in all parts of the skin and has been reported in sea turtles worldwide. Clinically infected individuals are often emaciated and anemic. In Mexico, however, there are few records of this disease. In this study of green turtles Chelonia mydas in Laguna San Ignacio in Baja California Sur (BCS), we noted one juvenile with multifocal fibropapilloma lesions on the external upper surface of its eyes and hind flippers. Light microscopy revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 42 publications
2
20
0
4
Order By: Relevance
“…External morphology and distribution of the observed neoplasms were consistent with previous descriptions of FP in green turtles [35]. The histopathological analysis revealed that the characteristics and proliferative changes observed in the skin lesions were similar to FP associated with viral particles [27], possibly a herpesvirus [11]; these proliferative changes indicates that are benign neoplasms. However, in this case the lesions could not be monitored to specify its change on size, preventing us to specify the stage of development of the FP [6] or if it was in phase of tumor regression [7]; even so, the neoplasms were registered as 1 (less than 5 cm), according to the classification of green turtles FP's proposed in [6,42] These cases are the fourth and fifth (respectively) recorded and studied by HP in the peninsula, but the first in an EPGT at LOL and the second in an olive ridley turtle at the GU.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…External morphology and distribution of the observed neoplasms were consistent with previous descriptions of FP in green turtles [35]. The histopathological analysis revealed that the characteristics and proliferative changes observed in the skin lesions were similar to FP associated with viral particles [27], possibly a herpesvirus [11]; these proliferative changes indicates that are benign neoplasms. However, in this case the lesions could not be monitored to specify its change on size, preventing us to specify the stage of development of the FP [6] or if it was in phase of tumor regression [7]; even so, the neoplasms were registered as 1 (less than 5 cm), according to the classification of green turtles FP's proposed in [6,42] These cases are the fourth and fifth (respectively) recorded and studied by HP in the peninsula, but the first in an EPGT at LOL and the second in an olive ridley turtle at the GU.…”
Section: Discussionsupporting
confidence: 87%
“…In Mexico, there have been reports of FP with clinical manifestation affecting olive ridley turtles in Colima and Oaxaca [40,41]. In BCS, at the GU two cases of FP with and without clinical manifestation were described in 2014 in an olive ridley turtle and a loggerhead turtle respectively [26]; in 2016, lesions of FP in a green turtle were described macroscopically and microscopically and identifying viral particles by TEM [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mexico, there are several studies related to sea turtles hematology [14,15,16,17]; however, regionally, in BCS, there are still few published works [18,7,13,19]. Thus, there is an urgent need to clearly indicate the health status and rate of diseases in regional sea turtle populations [8]. The present study was aimed at obtaining baseline information on selected health and disease indicators from the EPGT.…”
Section: Introductionmentioning
confidence: 99%
“…Actually these efforts were notably successful, and these stocks of EPGT appear to be in the process of recovery [6]. However, in 2014 and 2016 there are disease reports and mortality associated with illness [7,8]. Therefore, the idea of carrying out a program of health assessments to complement conservation efforts was proposed in order to minimize the threat of any potentially catastrophic disease outbreaks.…”
Section: Introductionmentioning
confidence: 99%